AKUNTABILITAS, TRANSPARANSI, DAN ANGGARAN BERBASIS KINERJA PADA SATUAN KERJA PERANGKAT DAERAH KOTA DENPASAR - Adiwirya, Muhammad Firdiansyah; Sudana, I Putu (E-Jurnal Akuntansi, 2015)
Performance-based budgeting is a budgeting that notices the priority programs and activities. In practice, it takes accountability and transparency so that the quality of the budget in accordance with the goals and objectives. The purpose of this research was to examine the effect of accountability and transparency in performance-based budgeting. This research was conducted in Denpasar by using questionnaires. Multiple linear regression was used as a technique of data analysis in this study. This study concluded that the accountability and transparency has simultaneous positive effect on performance-based budgeting. Partially, transparency has positive influence on performance-based budgeting. This study shows that the respondents have a more skewed perception of transparency compared with accountability.
Keywords: accountability, transparency, performance-based budgeting